Computer simulated approach to the formation of mixed coordinated complexes of DOPA with toxic metal ions. Issue 1 (1st January 2021) - Upadhyaya, Neerja; Nair (Ahuja), R.; Jain, Ruchi
Abstract : The potentiometric method is adopted to determine formation constants of complexes and used with a new numerical scheme. This study deals with the coordination behaviour of L-DOPA ((3, 4-dihydroxyphenyl)alanine) in Hg(II)/Pb(II)/Cd(II)-DOPA-L-alanine/glycine/L-phenylalanine (1:1:1) systems. DOPA is recognized as a neurotransmitter, and used in the treatment of Parkinson's disease. All the selected ligands are biologically active and play a vital role in the physiological processes. All the systems were investigated pH-metrically at 20±1°C and 30±1°C at three different ionic strengths in aqueous medium. Stability Constants of Generalized Species' computer program was used to obtain refined values of formation constants. Thermodynamic parameters (log k μ→ 0, Δ G o, Δ H o, Δ S o ) for biligand systems were calculated. The speciation of different species in mixed coordinated systems was obtained up to a specific pH in particular system. High values of formation constants support the formation of stable ternary complexes. Biligand complexes involving alanine were found to be the most stable, while those of phenylalanine were the least with lowest concentration at a particular pH in specific conditions. Results obtained are helpful in understanding the physiological behaviour of these systems.